(untitled) (Perner’s Contacts, 2010)
Solution of the start of an electric hoist is generally solved as the system with 2DOF; that is, translation motion of the hoist and rotational motion (swinging) of aload. However, in case of bulkier load can occur (e.g. due to wind forces) additionalrotation on the wire rope fitting and may cause exceeding of allowable angle of theload deflection. This detrimental swinging can affect service life of wire ropes. It isnecessary to receive better prerequisite for the solution of a swinging load.